Buying bad behavior: Tournament incentives and securities class action lawsuits. (7th July 2015) - Shi, Wei; Connelly, Brian L.; Sanders, Wm. Gerard
Abstract : Research summary: Tournament theory suggests that a large gap in pay between CEOs and top managers can provide incentives to perform, but we argue that it can also elicit negative effort and even motivate the kind of behavior that leads to lawsuits. We posit that this negative effort is greater when firms have high levels of unrelated diversification because there is less operational interdependency, so tournament effects are stronger. We also contend that the influence of tournament incentives on behavior leading to lawsuits is weaker when environmental uncertainty is high. We discuss the consequences of these findings for research on fraud and tournament theory as well as the practical repercussions for firms, investors, and policymakers. Managerial summary : Each year, the press has a field day when companies announce the outsized compensation packages laid out for CEOs. Economists use "tournament theory" to describe how high CEO pay motivates everyone else to work hard to get into the top job. The problem with this approach is that, yes, top managers work harder when the gap between their and the CEO's pay increases, but as that gap widens, it also incentivizes top managers to cheat or cut corners. As a result, we find that the gap between CEO and top manager compensation predicts the likelihood that shareholders will file a securities class action lawsuit against the company. This gap in pay is an especially good predictor of lawsuits for highly unrelated diversified companies and companies facing a low level of external uncertainty . Copyright © 2015 John Wiley & Sons, Ltd.